Kebijakan Pemberdayaan Perempuan: (Kajian Tentang Upaya Pemberdayaan Perempuan di Desa Buluh Cina Kecamatan Siak Hulu) - Wan Asrida; Erman M (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2014)
The Buluh Cina Village, one of eight villages located in the Distric Siak Hulu- Kampar Regency, is famous for its abundant natural resources. However, this village has high unemployement women (60 % ) and low educated women; thus it requires considerable efford by village goverment to empower them through policy, programme and activities, which could be realized by women.The women then could participate in the village development and assist the improvement of their family economy.